The Study of Distress of Recycling Pavement Road - Kittiwetvorakul, Queenaya; Jaritngam, Saravut (Princess of Naradhiwas University Journal, 2021)
This research aimed to study distress of pavement recycling road on highways in Songkhla province; 5 roads of Songkhla Highway District 1, 7 controlled sections, at a distance of 54.82 kilometers and Songkhla Highway District 2 (Na Mom); 2 roads, 3 controlled sections, at a distance of 16.93 kilometers. The research was conducted in 10 controlled sections with the total distance of 71.75 kilometers accounting for 10.79% of the distress roads, and there was a tendency for an increase. Prevent distress condition was inspected to analyze, clarify, and make a summary of types of distress. Analysis of relationship between the distress and factors affecting the pavement distress was made based on service life, road bed height, heavy truck amount and topography characteristics. The findings could be useful for road maintenance officers in Songkhla 1 Highway District and Songkhla 2 Highway District (Na Mom) when planning for maintenance and repair work, and when selecting using methods to prevent the damage in order to avoid more damage. It was found that there were 10 types of the distress of pavement repaired by pavement recycling methods on highways in Songkhla province, for example, Alligator Crack, Edge Joint Crack, Lane Joint Crack, Widening Crack, Raveling, Pot Hole, Rutting, Bleeding, Polished Aggregate, and Patching. The analysis of relationship between the distress and factors affecting the pavement distress revealed that there were two factors affecting the patterns of damage: service life and heavy truck amount.